Seven Years of Vitrified Blastocyst Transfers: Comparison of 3 Preparation Protocols at a Single ART Center - Levi Setti, Paolo Emanuele; Cirillo, Federico; De Cesare, Raffaella; Morenghi, Emanuela; Canevisio, Valentina; Ronchetti, Camilla; Baggiani, Annamaria; Smeraldi, Antonella; Albani, Elena; Patrizio, Pasquale (Frontiers in Endocrinology, 2020)
Introduction: Frozen–thawed embryo transfers (FET) have become a standard practice to increase cumulative pregnancy rates, however, the choice of the best preparation protocol remains a matter of debate. Design: Retrospective analysis of clinical pregnancy (CPR) and live birth rate (LBR) of FET in natural cycles (NC-FET), modified natural cycles with hCG-triggered ovulation (mNC-FET) and hormonal artificial replacement (AR-FET). Materials and Methods: For natural cycles, patients were monitored by ultrasound to evaluate the dominant follicle and by urinary LH sticks (NC-FET). When the endometrial thickness reached at least 7 mm and the dominant follicle 16–20 mm, hCG was administered in absence of urinary LH surge (mNC-FET). Embryo thawing and transfer was planned 7 days after LH surge or hCG administration. For the AR-FET, oral estradiol valerate was administered from day 2 of menstrual cycle until endometrial thickness reached at least 7 mm and transfer was planned after 5 days of vaginal progesterone. Only single vitrified blastocyst transfers were included. Results: In total 2,895 transfers were performed of which 561 (19.4%) carried out with NC-FET, 1,749 (60.4%) with mNC-FET and 585 (20.2%) with AR-FET. CPRs were 32.62%, 43.05% and 37.26%, respectively. LBRs were 24.06%, 33.56% and 25.81%, respectively. At multivariable analysis, a statistically significant (p<0.001) higher pregnancy outcome for mNC-FET versus NC-FET (OR 0.49 - 0.78) and AR-FET (OR 0.47 - 0.74) was observed. Conclusions: These results demonstrate a superior CPR and LBR following FET in hCG-triggered ovulation cycles compared to NC and AR-FET. However, these data need to be confirmed in randomized and prospective studies before definitive conclusions can be drawn.